2023
DOI: 10.1007/s10123-023-00384-8
|View full text |Cite
|
Sign up to set email alerts
|

An efflux pump in genomic island GI-M202a mediates the transfer of polymyxin B resistance in Pandoraea pnomenusa M202

Abstract: Background Polymyxin B is considered a last-line therapeutic option against multidrug-resistant gram-negative bacteria, especially in COVID-19 coinfections or other serious infections. However, the risk of antimicrobial resistance and its spread to the environment should be brought to the forefront. Methods Pandoraea pnomenusa M202 was isolated under selection with 8 mg/L polymyxin B from hospital sewage and then was sequenced by the PacBio RS II and Illum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…These secondary transporters rely on the energy generated by the electrochemical potential of the membrane to drive the efflux process. For example, a recent study indicated that GI-M202a, in conjunction with the MFS transporter in Pseudomonas pnomenusa , played a crucial role in facilitating the transmission of polymyxin B resistance ( Gao et al, 2023 ). The regulatory mutations result in the increased expression of efflux pumps and can cause MDR in the bacteria ( Huang et al, 2022 ; Lorusso et al, 2022 ).…”
Section: Biological Mechanism Of Drug Resistancementioning
confidence: 99%
“…These secondary transporters rely on the energy generated by the electrochemical potential of the membrane to drive the efflux process. For example, a recent study indicated that GI-M202a, in conjunction with the MFS transporter in Pseudomonas pnomenusa , played a crucial role in facilitating the transmission of polymyxin B resistance ( Gao et al, 2023 ). The regulatory mutations result in the increased expression of efflux pumps and can cause MDR in the bacteria ( Huang et al, 2022 ; Lorusso et al, 2022 ).…”
Section: Biological Mechanism Of Drug Resistancementioning
confidence: 99%